Developmental validation of forensic DNA-STR kits: Expressmarker 16 + 10Y and expressmarker 16 + 18Y. (September 2016) - Zhou, Huaigu; Bi, Gang; Zhang, Chen; Liu, Yanan; Chen, Ronghua; Li, Fayuan; Mei, Xinglin; Guo, Yulin; Zheng, Weiguo
Highlights: EX16 + 10Y and EX16 + 18Y PCR systems which combine autosomal and Y chromosome STR loci. The two systems are suitable for individual identification, paternity testing, paternal lineage testing and mixture identification. The two systems provide a new approach for fighting against crime quickly. Abstract: DNA-STR analysis is widely used in the forensic science field and obtaining results in shorter time is highly demanded. The developed forensic STR Kit, referred to as Expressmarker 16 + 10Y (EX16 + 10Y) and Expressmarker 16 + 18Y (EX16 + 18Y), could amplify the common autosomal and Y chromosome STR loci simultaneously. The kits are validated by a series of tests, including DNA mixtures, stutter ratios, PCR based studies, species specificities, inhibitors, sensitivity, sizing precision, reproducibility and parallel tests. The results demonstrated that EX16 + 10Y and EX16 + 18Y were useful tools for rapid criminal investigation.